2021
DOI: 10.1109/jiot.2020.3007070
|View full text |Cite
|
Sign up to set email alerts
|

On the Latency, Rate, and Reliability Tradeoff in Wireless Networked Control Systems for IIoT

Abstract: Wireless networked control systems (WNCSs) provide a key enabling technique for Industry Internet of Things (IIoT). However, in the literature of WNCSs, most of the research focuses on the control perspective, and has considered oversimplified models of wireless communications which do not capture the key parameters of a practical wireless communication system, such as latency, data rate and reliability. In this paper, we focus on a WNCS, where a controller transmits quantized and encoded control codewords to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 31 publications
0
40
0
Order By: Relevance
“…The Industrial Internet of Things (IIoT), as a subset of IoT, interconnects a multitude of industrial devices, actuators, and people at work. The fourth industrial revolution aims to tackle a set of new technological challenges in industrial control, automation and intelligence [1]. Currently, many of the data from the IIoT networks are processed and stored off-site in remote areas (i.e., cloud).…”
Section: A Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…The Industrial Internet of Things (IIoT), as a subset of IoT, interconnects a multitude of industrial devices, actuators, and people at work. The fourth industrial revolution aims to tackle a set of new technological challenges in industrial control, automation and intelligence [1]. Currently, many of the data from the IIoT networks are processed and stored off-site in remote areas (i.e., cloud).…”
Section: A Backgroundmentioning
confidence: 99%
“…Variable 𝜽 is shared across all agents. Decentralized RL tasks with parametrized approximation also fit in the same form as (1) only with the local loss as the expectation of individual cumulative costs.…”
Section: A Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent work on WNCS, authors have been increasingly exploring the inter-relation between the control and communication schemes. In [2] and [3], for example, the authors demonstrate how the latency and reliability trade-off directly impacts the system level stability, proposing a codesign of both control and communication entities. Specifically in [2], authors have demonstrated a counter-intuitive conclusion that the plant can still be stabilized with an arbitrarily large delay under certain channel conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In [2] and [3], for example, the authors demonstrate how the latency and reliability trade-off directly impacts the system level stability, proposing a codesign of both control and communication entities. Specifically in [2], authors have demonstrated a counter-intuitive conclusion that the plant can still be stabilized with an arbitrarily large delay under certain channel conditions. Another interesting finding was presented in [4], where authors elucidate an example how one can optimize long-term system performance by assuming more risks with less reliable transmissions in exchange for lower latency.…”
Section: Introductionmentioning
confidence: 99%